Problems of statistical evaluation of the volume of non-registered population of Kyiv - Pozniak O. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The statistic evaluation of the real population size in Kyiv based on data from government statistics on the number of de-jure population in the capital, taking into account information from other sources is done. Terms “nightly population” and “daily population” are introduced into scientific use.